Mass Spectrometric Identification of Adhesive Utilized in a Tian-tsui Tiara of the mid-Qing Dynasty (1776–1839 CE) in the Collection of the Tang Clan Folk Museum. (19th May 2019) - Zhu, Zhanyun; Tan, Panpan; Yang, Junchang; Ge, Hong; Liu, Liu
ABSTRACT: This study identified and interpreted an adhesive used in the making of a tiara of the mid-Qing Dynasty (1776–1839 CE), in the collection of the Tang Clan Folk Museum. By performance of mass spectrometry-based proteomics, a sample of adhesive residue was identified as bovine collagen proteins at the molecular level with high confidence. The result highlights the first example of accurate determination of the origin of the adhesive adopted in the tian-tsui craft, providing novel information and contributing to study of the significance, development, and exchange of tian-tsui craftsmanship.